Examining the Influence of Instructional Resources on English Language Reading Readiness of Children in Grade One at Kericho Rehabilitation School, Kenya. (Indonesian Journal of Early Childhood Education Studies, 2022)
Abstract English Language Reading Readiness (ELRR) is preparation of children by giving them the chance to improve the ability to listen, and speak effectively, to apply the desired vocabulary, and develop the appropriate academic readiness skills. English Language Reading Readiness is of great importance in improving equity in access to learning language and education results, particularly for juvenile delinquency. Children in rehabilitation schools have a vital social issue that every Nation tries to contain its control amongst the clear evidence, with the correct nurturing such as psychotherapeutic interventions is not provided to the young offenders, they may eventually graduate to hardcore criminals. An instructional resource is a generic term used to describe the materials that teachers use to deliver instruction. Teaching materials can support children’s learning and increase learner success. The objective of the study was to examine the influence instructional resources on English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School. The study also utilized the hypothesis which stated that there is no significant difference between mean score of the group of children taught before use of instructional resources, and mean score of the group of children taught after using instructional resources in English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School. However, little research has been done on the effect of instructional resources on English Language reading readiness in rehabilitation schools setting. The study adopted a case study research design that utilized a descriptive design. The target population included 1 Head teacher, 3 teachers and 25 learners in class 1 at the Kericho Rehabilitation School. Data collection was done using a combination of an English Language Reading Readiness Test, a questionnaire, document analysis and observation. The data was analyzed both descriptively and inferentially. The findings revealed that the null hypothesis was rejected and adopted the alternative hypothesis. The results show and it is recommended that the children’s performance in English Language Reading Readiness can be improved when the teachers effectively use instructional resources in the teaching of English language in rehabilitation schools. Key Words: Kenya, Kericho Rehabilitation School, Instructional Resources, Case study